A proposed new marikina shoe museum and training center - Lantaco, Mia Roxanne E. (Manila : National University, 2016)
Marikina City, one of the cities in Metro Manila, is known as the "Shoe Capital of the Philippines", for it is the biggest manufacturer of the shoes in the country.
Acknowledgement -- Certificate of endorsement -- Approval sheet -- Table of contents -- List of tables -- List of Figures -- List of maps -- List of graphs -- Abstract -- Chapter 1. The problem and its setting -- Chapter 2. Research methodology -- Chapter 3. Terms of references -- Chapter 4. Data gathering, collation and analysis of data -- Chapter 5. Design framework -- Chapter 6. Translations -- Chapter 7. Revisions and recommendations -- Bibliography -- Appendices.
Includes bibliographical references.
Keywords: SHOE -- MUSEUM; TRAINING CENTER